United States federal contracting and pollution prevention: how award type and facility characteristics affect adoption of source reduction techniques in four manufacturing sectors. (10th August 2021) - Hill, Dustin T; Petroni, Michael; Collins, Mary B
Abstract: There is reason to believe that hazardous emissions generated by industrial actors that have been awarded government contracts have different pollution prevention action patterns compared to those that have not been awarded government contracts. This is important because pollution prevention actions are a key inroad to alleviating environmental contamination generally and related human health effects. Specifically, we find that US-based industrial polluters tend to respond to Federal incentives to reduce costs by making efficiency improvements. Using publicly available purchasing, toxics release, and pollution prevention data from 2001 to 2012 for 458 081 transactions and 9910 facilities, we investigate the impact of contract award structure on facility environmental performance. We fit regression models to understand more about how the number of reported voluntary pollution prevention actions and reductions in total toxic chemical waste managed at each facility in terms of three types of contract awards. We find that industrial actors that have been awarded incentive contracts not only report more pollution prevention actions, but that these actions are more likely to result in significant pollution reduction. Results inform US Federal purchasing policy decisions and support earlier theoretical development at the intersection of ecological modernization, super-industrialization, and the role of government in facilitating transitions to green technology. In addition, greener purchasing decisions can have a broad impact on human health by reducing pollution in communities.